The C5a/C5a receptor 1 axis controls tissue neovascularization through CXCL4 release from platelets - Henry Nording (Nature Portfolio, 2021)
As more intersection points between platelets and the immune system are found, the role of platelets for vessel growth in the adult organism remains unclear. The authors demonstrate that platelets negatively modulate revascularization through CXCL4 secretion induced by activation C5aR1 on their surface.